lncRNA-LET Regulates Glycolysis and Glutamine Decomposition of Esophageal Squamous Cell Carcinoma Through miR-93-5p/miR-106b-5p/SOCS4 - Su, Xincheng; Xue, Cong; Xie, Chengke; Si, Xianzhe; Xu, Jie; Huang, Wenbo; Huang, Zhijun; Lin, Jianqing; Chen, Zhiyao (Frontiers in Oncology, 2022)
Background Dysregulated non-coding RNAs exhibit critical functions in various cancers. Nonetheless, the levels and corresponding functions of cirCSNX14 in esophageal squamous cell carcinoma (ESCC) yet remain to be elucidated. Methods Initially, the aberrant low levels of lncRNA-LET within ESCC tissues are validated via qRT-PCR observations. Moreover, the effects of lncRNA-LET upregulation on cell proliferation in vitro are determined. In addition, a series of assays determining the mechanistic views related to metabolism is conducted. Furthermore, the effects of lncRNA-LET in affecting tumor growth are investigated in vivo in a mouse model. Moreover, the interactions between lncRNA-LET and its networks are predicted and determined by RNA immunoprecipitation-assisted qRT-PCR as well as luciferase reporter assays. Results The downregulation of lncRNA-LET is correlated to the poor prognosis of ESCC patients. Moreover, the upregulated expression of lncRNA-LET could have reduced the cell viability. In vivo tumor inhibition efficacy assays showed that an increase of lncRNA-LET presented excellent inhibitory effects on cancer proliferation as reflected by tumor weight and volume in mice. Finally, the mechanistic views regarding the effects of miR-106b-5p or miR-93-5p and SOCS4 on ESCC are related to the feedback of lncRNA-LET. Conclusion Collectively, this study suggested that lncRNA-LET miR-93-5p or the miR-106b-5p–SOCS4 axis may provide great potential in establishing ESCC therapy.